Intergenerational Transfers in Infant Mortality in Southern Sweden, 1740-1968 - Luciana Quaranta (Historical Life Course Studies)
Studies conducted in historical populations and developing countries have evidenced the existence of clustering in infant deaths, which could be related to genetic inheritance, early life exposures, and/or to social and cultural factors such as education, socioeconomic status or parental care. A transmission of death clustering has also been found across generations. This paper is one of five studies that analyses intergenerational transmissions in infant mortality by using a common program to create the dataset for analysis and run the statistical models with data stored in the Intermediate Data Structure. The results of this study show that in five rural parishes in Scania, the southernmost province of Sweden, during the years 1740-1968 infant mortality was transmitted across generations. Children whose maternal grandmothers experienced two or more infant deaths had higher risks of dying in infancy. The results remained consistent when restricting the sample only to cases where the grandmother had been observed for her entire reproductive history or when controlling for socioeconomic status. When running sex specific models, significant effects of the number of infant deaths of the grandmother were observed for girls but not for boys.